The Tax Compliance Factors In Individual Taxpayer Perspective - Donny Maha Putra (Universitas Pendidikan Indonesia, 2023)
Main Purpose - This study examines the effect of understanding tax regulations (UTR), tax digitalization (TDigi), and taxpayer awareness (TAWs) on taxpayer compliance (TC).Method - A questionnaire was used for testing with 399 samples of individual taxpayers in Indonesia selected using simple random sampling. The data were analyzed using Structural Equation Modeling with Lisrel 8.8 statistical tool.Main Findings - It was found that Tdigi is the most significant determinant of TC, followed by UTR. Meanwhile, TAWs has no significant effect on TC. It is implied that TDigi plays a significant role.Theory and Practical Implications - Interestingly, this study found that the effect of TAWs on TC was not significant. It is revealed that TAWs can be formed if the public understands that the taxes paid are used by the government for people's welfare and will return to them. Novelty - This studi explains the relationship between research variables and attribution theory that internal factors can affect TC in carrying out their tax obligations